Analisis Hasil Produksi Teks Berita Kelas XI F2B di SMA Negeri 11 Muaro Jambi - Aeni Nur Fitriana (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
This study aims to provide a comprehensive overview of the ability of class XI F2B students at SMA Negeri 11 Muaro Jambi in producing news texts. The focus of the study includes analysis of text structure, the completeness of the 5W + 1H elements, and the use of linguistic rules in accordance with news text writing standards. The approach used in this study is descriptive qualitative, by analyzing the news texts written by students. Based on the results of the study, students have understood the basic structure of news texts, especially in writing titles and leads, which are in accordance with general provisions. However, there are quite significant weaknesses in the 5W + 1H elements, especially in the elements of "why" and "how" which are often not included or written in less depth, thus reducing the completeness of information in the compiled news. In addition, errors in the use of standard language, choice of diction, and the construction of effective sentences are still frequently found. This study shows that to improve the quality of news writing, it is necessary to strengthen news writing learning through intensive practice, collaborative learning between students, and increasing student information literacy. This is expected to improve students' ability to produce news texts that are more complete, accurate, and in accordance with journalistic principles.